Endovascular thrombectomy of calcified emboli in acute ischemic stroke: a multicenter study - Maurer, Christoph J.; Dobrocky, T.; Joachimski, F.; Neuberger, Ulf; Demerath, T.; Brehm, A.; Cianfoni, A.; Gory, B.; Berlis, A.; Gralla, J.; Möhlenbruch, Markus Alfred; Blackham, K. A.; et al. (American journal of neuroradiology, 2020)
Background and purpose: Large intracranial vessel occlusion due to calcified emboli is a rare cause of major stroke. We assessed the prevalence, imaging appearance, the effectiveness of mechanical thrombectomy, and clinical outcome of patients with large-vessel occlusion due to calcified emboli. - Materials and methods: We performed a retrospective analysis of clinical and procedural data of consecutive patients who underwent mechanical thrombectomy due to calcified emboli in 7 European stroke centers. - Results: We screened 2969 patients, and 40 patients matched the inclusion criteria, accounting for a prevalence of 1.3%. The mean maximal density of the thrombus was 327 HU (range, 150-1200 HU), and the mean thrombus length was 9.2 mm (range, 4-20 mm). Four patients had multiple calcified emboli, and 2 patients had an embolic event during an endovascular intervention. A modified TICI score of ≥2b was achieved in 57.5% (23/40), with minimal-to-no reperfusion (modified TICI 0-1) in 32.5% (13/40) and incomplete reperfusion (modified TICI 2a) in 10% (4/40). Excellent outcome (mRS 0-1) was achieved in only 20.6%, functional independence (mRS 0-2) in 26.5% and 90-day mortality was 55.9%. - Conclusions: Acute ischemic stroke with large-vessel occlusion due to calcified emboli is a rare entity in patients undergoing thrombectomy, with considerably worse angiographic outcome and a higher mortality compared with patients with noncalcified thrombi. Good functional recovery at 3 months can still be achieved in about a quarter of patients.